2010
DOI: 10.5455/msm.2010.22.168-171
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Information Systems

Abstract: REVIEW SUMMARYComputer technology is a reality of our modern world. It gives us a tool which can be used to help us cope with the complexity and efficiency which is often required in many areas of work. It is an erroneous assumption that it robs a situation of its human qualities. No one would deny that the use of a word processor denies the possibility of highly creative writing being produced or that computerized checkouts make the interaction skills of the checkout person irrelevant to the process of strugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A nursing information system is a computer-based integrated system with a storage for clinical and demographic data that predicates the activities of nursing and patient care outcomes, organizes data in accordance with the need in information structures, and provides access to related knowledge bases and patients’ data ( 6 ). The main functions of a nursing information system include: care planning, nursing clinical recording, care assessment, discharge planning, personnel management, staff list, attendance record, cost and budget management, and management of complex skills (Skillmix) ( 7 ). The results of research conducted in North Africa showed, nursing information systems need better technology to develop, and most of the systems implemented in terms of technology have problems ( 8 ), because in addition to the need for access to a computer, an optimized use of these systems requires the presence of new technology tools such as barcode scanner equipment, RFID, advanced equipment for word processing, special software tools such as off-line inquiry software ( 9 ), the presence of LAN network communication and integration between systems ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…A nursing information system is a computer-based integrated system with a storage for clinical and demographic data that predicates the activities of nursing and patient care outcomes, organizes data in accordance with the need in information structures, and provides access to related knowledge bases and patients’ data ( 6 ). The main functions of a nursing information system include: care planning, nursing clinical recording, care assessment, discharge planning, personnel management, staff list, attendance record, cost and budget management, and management of complex skills (Skillmix) ( 7 ). The results of research conducted in North Africa showed, nursing information systems need better technology to develop, and most of the systems implemented in terms of technology have problems ( 8 ), because in addition to the need for access to a computer, an optimized use of these systems requires the presence of new technology tools such as barcode scanner equipment, RFID, advanced equipment for word processing, special software tools such as off-line inquiry software ( 9 ), the presence of LAN network communication and integration between systems ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing information systems (NISs) are essential parts of hospital information systems. Nursing information systems support the clinical, administrative, and managerial activities of nursing staff, 1 as well as contribute to improvements in clinical nursing practice. Utilization of NISs ensures high-quality information and anytime access, 2 empowering nurses to maintain situational awareness and make ad hoc decisions 3,4 .…”
mentioning
confidence: 99%
“…Computer technology gives us a tool which can be used to help us cope with the complexity and efficiency which is often required in many areas of work [2]. Since the earliest days of technology adoption in health care, nursing informatics professionals have been at the forefront of leading change.…”
Section: Introductionmentioning
confidence: 99%